Telaah Dakwah Virtual Sebagai Perkembangan Metode Dakwah Islam di Era Modern - Hafidz Idri Purbajati (MODELING: Jurnal Program Studi PGMI, 2021)
Religius through social media or called virtual Religius is one form of method development in Religius. The emergence of this new culture attracted the attention of researchers to examine virtual Religius. as the development of Religius. methods in the modern era. The research method used is descriptive qualitative which tries to describe how virtual Religius is the development of Religius methods nowadays, while the data collection technique uses library research that uses relevant books as primary and secondary data sources. This study resulted that virtual Religius. through social media as the development of Religius methods was carried out by paying attention to Religius marches, Religius media, Religius concepts and strategies, and paying attention to the cultural elements of the community.